Characterization and process optimization study on physicochemical and functional properties changes in oil isolates dried under various temperature and time - Kang, Yi Jin (2023)

(untitled)
The increasing human population causing food supply to be insufficient. Due to high nutritional values of edible insects, it has been studied by researchers in the world to prevent the insufficient food supply. In this study, the objectives are to examine the effect of drying time and temperature of the oil properties, optimize the drying parameters by using Response Surface Methodology (RSM), and characterize the changes on the functional properties of oil. The targeted edible insect use in this study is Black Soldier Fly prepupae (BSFP) which were fed with fruit waste. Based on the optimization results, the moisture loss was 65.31 % at 100 °C and 34.70 hours, crude lipid yield was 49.79 % at 88.29 °C and 29.82 hours, browning index was measured to have a value of 294.70 at 100 °C and 48 hours, iodine value of 23.70 gI2/ 100g at 90.89 °C and 34.82 hours. Meanwhile, the optimized peroxide value obtained was 8.20 mEq O2/ kg at 100 °C and 48 hours, and DPPH Free Radical Scavenging Assay (antioxidant activity) of 76.14 % and 99.60 °C and 47.93 hours. In conclusion to this study, the oven dried prepupae undergo different drying parameters of 80 °C to 100 °C and 24 hours to 48 hours, produced a maximized crude lipid of 49.74 % at 88.29 °C and 29.82 hours.